Acceptance and Commitment Therapy (ACT) to reduce depression: A systematic review and meta-analysis - Bai, Zhenggang; Luo, Shiga; Zhang, Luyao; Wu, Sijie; Chi, Iris (Journal of affective disorders, 2020)
•Previous systematic reviews including depression or anxiety population have provided evidence for the effectiveness of ACT as a psychological intervention for depression disease when compared with no intervention.•Our study searched six databases, and finally included 18 studies with low risk and bias, which make the results more comprehensive, accurate and credible compared with previous studies.•This review investigated the effectiveness of ACT on depression reduction and further examine the relationship between different follow-up periods, different degree of depression, and different age of patients through subgroup analysis. The aim of this study is to investigate the effectiveness of ACT on depression reduction and further examine the relationship between different follow-up periods, different degree of depression, and different age of patients through subgroup analysis. Relevant electronic databases were searched from Jan 2010 to Aug 2018, including CNKI, WANFANG, PubMed, EMBASE, Cochrane Library, PsycINFO. Two reviewers independently screened for eligible studies, extracted data, and assessed risk of bias of the included studies. The Cochrane Collaboration's bias assessment tool was used to evaluate the risk of bias for included studies, and Review Manager 5.3 Software for the meta-analysis 18 studies with 1,088 participants were included in the review. Four studies were rated as high-quality studies, and the remaining 14 studies were rated as moderate quality studies. ACT significantly reduced depression as compared with the control group [SMD = 0.59, 95% CI (0.38, 0.81)]. The subgroup analysis found a significant difference between ACT and control group after post-intervention, three months follow up, mild depression group and adults group, [SMD= 0.62, 95% CI (0.35, 0.90), [SMD= 0.55, 95% CI (0.23, 0.87)], [SMD= 0.65, 95% CI (0.40, 0.91)], [SMD= 0.52, 95% CI (0.33, 0.71)] respectively. The heterogeneity between included studies results in heterogeneity of the results. Most of the specific methods for random sequence generation and allocation concealment were not clear. The search results had limitations since only the published studies in Chinese and English were searched and lacked a search for gray and paper documents. The current study suggested that ACT was significantly for reducing depressive symptoms compared with the control group, especially at three months of follow-up, adult group and mild depression. More research is needed to investigate the difference effects for minor group, moderate and severe depression and long-term follow-up.